Correcting the Corneal Power Measurements after Myopic Laser In Situ Keratomileusis - 刘磊 董洁玉 李新宇 (Journal of Huazhong University of Science and Technology. Medical sciences, 2006)
Summary： To describe and evaluate a refraction-derived method and a clinically derived method to calculate the correct corneal power for intraocular lens （IOL） power calculations after laser in situ keratomileusis （LASIK） and to compare the results to the commonly used history-derived method. Retrospective analysis were conducted in consecutive case from clinical practice. For each patient, we established the pre-LASIK and postzLASIK spectacle refraction, the pre-LASIK （Kpre） and post-LASIK K readings （Kpost）. We then calculated the pre- and post-LASIK refraction at the corneal plane and the amount of correction obtained by the refraction surgery （ASEQco）. The cases were divided into two groups. Group Ⅰ was used to derive two formulas. The values obtained with the two methods were compared with the K by history-derived method （Kc.hd） in group Ⅱ to validate the results. The K values calculated by using the refraction-derived method （Kc.rd） and the K values calculated using the clinically derived method （Kc.cd） correlated highly with Kcho. The correct corneal power for intraocular lens （IOL） power calculations after LASIK can use refraction-derived method and clinically derived method instead of history-derived method when some refractive parameters are not available.